An assessment of integrated management of childhood illness (MCI) screening for aids based on who criteria and modifications using a retrospective review of paediatric case records from Edenvale Hospital. - Win, Thein (My University, 2006)
The study aimed to evaluate IMCI guidelines, developed to assess children with Suspected Symptomatic HIV [SSHIV] as a screening tool for AIDS. OBJECTIVES 1. To look at the agreement between IMCI classification for SSHIV and WHO clinical case definition for AIDS using a retrospective record review of the same hospitalised children. 2. To determine the sensitivity, specificity, positive predictive values and likelihood ratios of the IMCI SSHIV criteria (Guidelines 2001), WHO clinical case definition for paediatric AIDS and Bloemfontein Proposed simplified case definition for paediatric SSHIV, using HIV ELISA results in children older than 15 months as a gold standard. METHODS The study involved 304 children in the IMCI age range who were admitted to the Edenvale Hospital during the study period and who met all the inclusion and exclusion criteria. These children were assessed with IMCI criteria and WHO criteria for AIDS. [Objective 1] The findings of 50 children above 15 months of age with ELISA results were compared using 3 sets of criteria. [IMCI, WHO and Bloemfontein proposed simplified case definition for paediatric SSHIV] [Objective 2] FINDINGS IMCI and WHO criteria for AIDS were the same in 158 [52%] of the 304 children. Almost all [22 out of 23 children] with WHO criteria for AIDS were also classified by IMCI criteria as Suspected Symptomatic HIV. [Objective 1] v IMCI criteria had the highest sensitivity [85.7%], while WHO criteria had the highest specificity [88%] based on ELISA results. [Objective 2] CONCLUSION Based on the above findings, IMCI criteria could be considered as a screening tool to select children aged 15 months and above for appropriate laboratory investigation for HIV infection confirmation in remote areas. WHO criteria for AIDS could be considered for exclusion of AIDS in children aged 15 months and above in remote areas where laboratory facilities are not available. In this study, reliable findings could not be obtained in children younger than 15 months.
Faculty of Health Science SChool of Public Health 0112677r burmamtk@iafrica.com
Keywords: IMCI; AIDS; WHOCRITERIA